2022
DOI: 10.1002/aenm.202202298
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐Slip Derived Network Topology to Remarkable Strength–Toughness Combination of Perovskite Film for Flexible Solar Cells

Abstract: The toughness and strength are generally mutually exclusive for most materials. Although the biological materials in nature such as wood, bone, and nacre exhibit outstanding toughness by forming hierarchical multiscale (nano to macro) structures, it is a huge challenge to simultaneously obtain excellent strength and toughness from material synthesis. Here, one kind of network topology is observed by introducing sodium hyaluronate into organometallic halide perovskite film to greatly improve its strength and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Additives help passivating defects in perovskites and improving the mechanical stability of inverted FPSCs. [84,90,97,[175][176][177][178] Generally, introducing cations of different sizes into perovskites causes microstrain of c) Reproduced with permission. [169] Copyright 2021, Wiley-VCH.…”
Section: Additive Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Additives help passivating defects in perovskites and improving the mechanical stability of inverted FPSCs. [84,90,97,[175][176][177][178] Generally, introducing cations of different sizes into perovskites causes microstrain of c) Reproduced with permission. [169] Copyright 2021, Wiley-VCH.…”
Section: Additive Engineeringmentioning
confidence: 99%
“…Additives help passivating defects in perovskites and improving the mechanical stability of inverted FPSCs. [ 84,90,97,175–178 ] Generally, introducing cations of different sizes into perovskites causes microstrain of perovskite films, which affects the optoelectronic properties of inverted FPSCs. Yan et al reported a method of alleviating microstrain in perovskite films by additive engineering.…”
Section: Perovskite Active Layersmentioning
confidence: 99%
“…For optoelectronic materials, it is difficult to resolve the contradiction between toughness and strength while maintaining high optoelectronic properties. [163,164] Lu et al [165] designed a network topology that simultaneously improved the strength and flexibility of perovskite films. The designed sodium hyaluronate (SH) hydrogel is composed of a strong polymer network and is highly elastic.…”
Section: Light Absorbing Layermentioning
confidence: 99%
“…g) The summary of normalized PCE and different bending conditions of recently reported f-PSCs. Reproduced with permission [165]. Copyright 2022, Wiley-VCH.…”
mentioning
confidence: 99%
“…For this reason, Lu et al designed a topological structure in which perovskite crystal particles were entangled with sodium hyaluronate (SH). [ 133 ] During the microstructure evolution of the film, the strong interaction between perovskite and SH connects the subgrains to form a network topology. This network structure achieves significantly enhanced toughness and strength of perovskite films.…”
Section: Additive Engineering In Fpscsmentioning
confidence: 99%